2019
DOI: 10.3389/fcimb.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

A Pertussis Outer Membrane Vesicle-Based Vaccine Induces Lung-Resident Memory CD4 T Cells and Protection Against Bordetella pertussis, Including Pertactin Deficient Strains

Abstract: Pertussis is a respiratory infectious disease that has been resurged during the last decades. The change from the traditional multi-antigen whole-cell pertussis (wP) vaccines to acellular pertussis (aP) vaccines that consist of a few antigens formulated with alum, appears to be a key factor in the resurgence of pertussis in many countries. Though current aP vaccines have helped to reduce the morbidity and mortality associated with pertussis, they do not provide durable immunity or adequate protection against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 63 publications
0
55
0
4
Order By: Relevance
“…This trend continued as the same group compared pertussis rates among adolescents who received the Tdap booster, which consists of a lower concentration of vaccine antigens with the addition of Fim antigen. These studies found that Tdap effectiveness dropped from 69% the first year after vaccination to an alarming 9% after 4 years 36 . Predictably, a study found that individuals who only received DTaP immunizations compared to those who received the wP vaccine schedule were at greater risk of contracting pertussis 37 .…”
Section: Waning Dtap Vaccinementioning
confidence: 98%
See 4 more Smart Citations
“…This trend continued as the same group compared pertussis rates among adolescents who received the Tdap booster, which consists of a lower concentration of vaccine antigens with the addition of Fim antigen. These studies found that Tdap effectiveness dropped from 69% the first year after vaccination to an alarming 9% after 4 years 36 . Predictably, a study found that individuals who only received DTaP immunizations compared to those who received the wP vaccine schedule were at greater risk of contracting pertussis 37 .…”
Section: Waning Dtap Vaccinementioning
confidence: 98%
“…Current and past B. pertussis immune response studies have focused on a limited set of known immunological responses to B. pertussis challenge such as: bacterial burden, antibody response, recruitment of phagocytes, cytokine profiles, and others 35,36 .…”
Section: Characterizing the Gene Expression Profiles Of The Lungs Of mentioning
confidence: 99%
See 3 more Smart Citations